Reorientation mechanisms of block copolymer/CdSe quantum dot composites under application of an electric field. Issue 40 (15th September 2016) - Kathrein, Christine C.; Pester, Christian; Ruppel, Markus; Jung, Maike; Zimmermann, Marc; Böker, Alexander
Abstract : In situ birefringence measurements reveal the effect of nanoparticles on the electric field-induced alignment of a microphase separated block copolymers. Abstract : Time- and temperature-resolved in situ birefringence measurements were applied to analyze the effect of nanoparticles on the electric field-induced alignment of a microphase separated solution of poly(styrene)- block -poly(isoprene) in toluene. Through the incorporation of isoprene-confined CdSe quantum dots the reorientation behavior is altered. Particle loading lowers the order–disorder transition temperature, and increases the defect density, favoring nucleation and growth as an alignment mechanism over rotation of grains. The temperature dependent alteration in the reorientation mechanism is analyzed via a combination of birefringence and synchrotron SAXS. The detailed understanding of the effect of nanoparticles on the reorientation mechanism is an important prerequisite for optimization of electric-field-induced alignment of block copolymer/nanoparticle composites where the block copolymer guides the nanoparticle self-assembly into anisotropic structures.